A method for preparing a positive electrode material for a polyanion sodium ion battery

By using spray drying and sintering processes in the positive electrode material of sodium ion battery, NASICON structural materials containing barium are prepared, which solves the problem of low electronic conductivity of existing materials and improves the rate performance and cycle stability.

CN114243012BActive Publication Date: 2025-01-10GUANGDONG BRUNP RECYCLING TECH CO LTD +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111246976.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-26
Publication Date
2025-01-10
Estimated Expiration
2041-10-26

AI Technical Summary

Technical Problem

The electronic conductivity of existing sodium ion battery positive electrode materials is low, resulting in unsatisfactory rate performance and it is difficult to meet the demand for large current charging and discharging.

Method used

Using a preparation method of a polyanionic sodium ion battery positive electrode material, the phosphorus source, vanadium source, sodium source and carbon source are dissolved in water and spray-dried, and then mixed with the barium source dissolved by organic acid, evaporate and sintering. By processing, a barium-containing NASICON structural material was prepared to enhance the electron conductivity and rate performance.

Benefits of technology

The electronic conductivity and rate performance of the positive electrode material of sodium ion battery is improved, the unit cell volume is increased, the unit cell structure is stabilized, the generation of dead sodium ions is reduced, and the circulation performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114243012B_ABST
    Figure CN114243012B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a positive electrode material for a polyanion type sodium ion battery, comprising dissolving a phosphorus source, a vanadium source, a sodium source, and a carbon source in water, spray drying, and preparing particles, dissolving a barium source in an organic acid to obtain a solution A, evaporating the solution A to obtain a solid B, adding the solid B to ethanol to dissolve, and preparing a solution C, mixing the particles with the solution C, and then performing an evaporation treatment to obtain a dry material, and sintering the dry material under air-tight conditions to obtain a positive electrode material for a polyanion type sodium ion battery. The positive electrode material for a polyanion type sodium ion battery prepared by the invention is doped with barium atoms with a larger radius, which increases the unit cell volume, makes it easy for sodium ions to be deintercalated, and produces less sodium ions with dead sodium, thereby improving the rate performance, and the barium ion radius is large, which can stabilize the unit cell more; the phosphorus source, the vanadium source, the sodium source, and the carbon source are dissolved in water and then spray dried to prepare balls, so that various materials can be evenly mixed, and homogeneous generation can be achieved during sintering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a method for preparing a positive electrode material of a polyanion sodium ion battery. Background Art

[0002] Sodium-ion batteries have the same principle and structure as lithium-ion batteries, and are both composed of positive electrode materials, negative electrode materials, electrolytes and separators. When the battery is charged and discharged, Na+ is embedded and deintercalated back and forth between the two electrodes: when the battery is charged, Na+ is deintercalated from the positive electrode, embedded in the negative electrode through the electrolyte, and the negative electrode is in a sodium-rich state.

[0003] Sodium and lithium are in the same main group and have similar chemical properties. The content of sodium in the earth's crust is much higher than that of lithium. Therefore, the development of sodium-ion batteries can alleviate the problem of lithium resource shortage to a certain extent, and have a greater market competitive advantage. Therefore, the research and development of sodium-ion battery electrode materials has gradually become a hot topic in energy storage research. The sodium storage cathode materials reported so far mainly include polyanionic compounds, Prussian blue sodium salts and transition metal oxides. Transition metal oxides include sodium cobaltate, sodium manganate, etc., which are characterized by high capacity, but poor cycle performance, especially at high voltage, poor overcharge resistance and thermal stability. Prussian blue sodium salts are a type of complex containing variable valence transition metals. This type of compound has a complete cubic crystal form, a three-dimensional spatial structure, and a large number of coordination vacancies, which is conducive to the reversible extraction and embedding of sodium ions, but the capacity decay mechanism of this type of compound is still unclear, and the performance needs to be improved.

[0004] Polyanionic compounds mainly include transition metal (pyro)phosphates, fluorophosphates, etc. Among them, polyanionic phosphate materials may become the best positive electrode materials for sodium ion batteries due to their stable structure and high working voltage. In particular, the recently developed sodium vanadium phosphate with NASICON structure Na 3 V 2 (PO 4 ) 3 (NVP) positive electrode material has a strong competitive advantage, and its 3.4V voltage platform is significantly higher than most other sodium-ion battery positive electrode materials. However, NVP has a relatively low electronic conductivity, resulting in less than ideal rate performance. Therefore, how to improve the electronic conductivity of active materials and improve high-current charge and discharge performance is a key difficulty in the promotion and application of sodium-ion batteries. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a method for preparing a polyanion type sodium ion battery positive electrode material, which can improve the conductivity and rate performance of such positive electrode material.

[0006] According to one aspect of the present invention, a method for preparing a polyanion type sodium ion battery positive electrode material is provided, comprising the following steps:

[0007] The phosphorus source, vanadium source, sodium source and carbon source are dissolved in water and then spray-dried to prepare particles;

[0008] The barium source is dissolved in an organic acid to obtain a solution A, the solution A is evaporated to obtain a solid B, and the solid B is added to ethanol to dissolve to obtain a solution C;

[0009] The particles are mixed with solution C and evaporated to dryness to obtain a dry material;

[0010] The dried material is sintered in an air-tight condition to obtain the polyanion type sodium ion battery positive electrode material.

[0011] In some embodiments of the present invention, the phosphorus source is at least one of sodium pyrophosphate, phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, sodium monohydrogen phosphate or sodium dihydrogen phosphate.

[0012] In some embodiments of the present invention, the vanadium source is at least one of vanadium trioxide, vanadium pentoxide, ammonium metavanadate, vanadyl acetylacetonate or vanadium acetylacetonate.

[0013] In some embodiments of the present invention, the sodium source is at least one of sodium carbonate, sodium acetate, sodium oxalate, sodium pyrophosphate, sodium monohydrogen phosphate or sodium dihydrogen phosphate.

[0014] In some embodiments of the present invention, the carbon source is at least one of glucose, citric acid, oxalic acid, lactose or galactose.

[0015] In some embodiments of the present invention, the amount of water added is 2-10 times the total mass of the phosphorus source, vanadium source, sodium source and carbon source.

[0016] In some embodiments of the present invention, the molar ratio of Na, V and P elements in the sodium source, vanadium source and phosphorus source is (1-5): (1.01-1.2): (2-4).

[0017] In some embodiments of the present invention, the molar ratio of the carbon source to the vanadium source is 1-2.

[0018] In some embodiments of the present invention, the inlet temperature of the equipment used for spray drying is 220±20°C, the outlet temperature is 110±10°C, and the feed rate is 40-80Kg / h.

[0019] In some embodiments of the present invention, the barium source is at least one of barium carbonate and barium hydroxide; preferably, the molar ratio of the barium element in the barium source to the vanadium element in the vanadium source is (0.01-0.2):1.

[0020] In some embodiments of the present invention, the organic acid is at least one of citric acid, formic acid, acetic acid or propionic acid.

[0021] In some embodiments of the present invention, the volume concentration of ethanol is ≥95%.

[0022] In some embodiments of the present invention, the sintering is to keep the dried material at 450-500°C for 2-4 hours, and then raise the temperature to 550-800°C for 8-12 hours. The temperature is controlled to be kept at 450-500°C for 2-4 hours, so that the organic acid barium reacts with the vanadium source to generate trigonal barium vanadate with a lower dielectric constant, further enhancing the conductivity of the material obtained by subsequent sintering; the temperature is controlled to be kept at 550-800°C for 8-12 hours to further ensure that the reaction is fully carried out and a stable crystalline phase structure is formed.

[0023] In some embodiments of the present invention, the dried material is ground after sintering, and the grinding time is 1-2 hours.

[0024] According to a preferred embodiment of the present invention, at least the following beneficial effects are achieved:

[0025] 1. The polyanion type sodium ion battery positive electrode material prepared by this method is doped with barium atoms with a larger radius, which increases the unit cell volume, makes it easier for sodium ions to be deintercalated, and produces less dead sodium, thereby improving the rate performance. In addition, the barium ion has a large radius and can better stabilize the unit cell.

[0026] 2. The phosphorus source, vanadium source, sodium source and carbon source are dissolved in water and then spray-dried to form balls, so that various materials can be evenly mixed and homogeneous generation can be achieved during sintering.

[0027] 3. After the barium source is dissolved with an organic acid, the obtained organic barium acid can be dissolved in ethanol and mixed with the spherical particles obtained by spraying. Under the action of ethanol, the organic barium acid penetrates into the particles to make all the materials evenly mixed. Then, the ethanol is evaporated and recovered by utilizing its volatile characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0029] Figure 1 This is a SEM image of the polyanion sodium ion battery positive electrode material of Example 1 of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0031] Example 1

[0032] This example prepares a polyanion type sodium ion battery positive electrode material, and the specific process is as follows:

[0033] (1) 3.5 kg of ammonium dihydrogen phosphate, 1.80 kg of ammonium metavanadate, 2.07 kg of sodium acetate, and 2.8 kg of glucose were dissolved in 80 L of pure water, and then spray-dried. The inlet temperature of the spray-drying equipment was adjusted to 220 ± 20 °C, the outlet temperature was adjusted to 110 ± 10 °C, and the feed rate was 80 kg / h to prepare spherical particles;

[0034] (2) dissolving 0.045 kg of barium carbonate in acetic acid until it is completely dissolved to obtain solution A;

[0035] (3) evaporating solution A to obtain solid B, adding solid B into 98% ethanol by volume until it is completely dissolved to obtain solution C;

[0036] (4) mixing the spherical particles prepared in step (1) and solution C uniformly, evaporating the mixture to obtain a dry material, and recovering ethanol;

[0037] (5) Keep the dried material isolated from air at 450°C for 3 hours, then raise the temperature to 600°C and keep it for 9 hours;

[0038] (6) The sintered material was added to a ball mill and ground for 1 hour to obtain a polyanion sodium ion battery positive electrode material with a chemical formula of NaBa 0.015 V 1.01 (P 2 O 7 ) 0.03 / C.

[0039] The positive electrode material prepared in this embodiment is used as the working electrode, sodium is used as the counter electrode, and a button-type battery is assembled. At a current density of 80 mA / g, the first cycle specific capacity is 66 mAh / g. After 50 cycles, the specific capacity can be maintained at 54 mAh / g.

[0040] Example 2

[0041] This example prepares a polyanion type sodium ion battery positive electrode material, and the specific process is as follows:

[0042] (1) 3.5 kg of sodium dihydrogen phosphate, 1.25 kg of ammonium metavanadate, and 1.44 kg of oxalic acid were dissolved in 45 L of pure water, and then spray-dried. The inlet temperature of the spray-drying equipment was adjusted to 220 ± 20 °C, the outlet temperature was adjusted to 110 ± 10 °C, and the feed rate was adjusted to 60 kg / h to prepare spherical particles.

[0043] (2) dissolving 0.29 kg of barium carbonate in acetic acid until it is completely dissolved to obtain solution A;

[0044] (3) evaporating solution A to obtain solid B, adding solid B into 98% ethanol by volume until it is completely dissolved to obtain solution C;

[0045] (4) mixing the spherical particles prepared in step 1 and solution C uniformly, evaporating the mixture to obtain a dry material, and recovering ethanol;

[0046] (5) The dried material is isolated from air and maintained at 500°C for 4 hours, then the temperature is increased to 550°C and maintained for 12 hours.

[0047] (6) The sintered material was added to a ball mill and ground for 1.5 hours to obtain a polyanion type sodium ion battery positive electrode material with a chemical formula of Na 6 Ba 0.3 V 2.2 (P 2 O 7 ) 3 O 0.6 / C.

[0048] The positive electrode material prepared in this embodiment is used as the working electrode, sodium is used as the counter electrode, and a button-type battery is assembled. At a current density of 80 mA / g, the first cycle specific capacity is 68 mAh / g. After 50 cycles, the specific capacity can be maintained at 61 mAh / g.

[0049] Example 3

[0050] This example prepares a polyanion type sodium ion battery positive electrode material, and the specific process is as follows:

[0051] (1) 3.5 kg of ammonium dihydrogen phosphate, 1.6 kg of ammonium metavanadate, 3.57 kg of sodium oxalate, and 4.93 kg of glucose were dissolved in 100 L of pure water, and then spray-dried. The inlet temperature of the spray-drying equipment was adjusted to 220 ± 20 °C, the outlet temperature was adjusted to 110 ± 10 °C, and the feed rate was adjusted to 40 kg / h to prepare spherical particles.

[0052] (2) dissolving 0.675 kg of barium carbonate in acetic acid until it is completely dissolved to obtain solution A;

[0053] (3) evaporating solution A to obtain solid B, adding solid B into 98% ethanol by volume until it is completely dissolved to obtain solution C;

[0054] (4) mixing the spherical particles prepared in step 1 and solution C uniformly, evaporating the mixture to obtain a dry material, and recovering ethanol;

[0055] (5) The dried material is isolated from air and kept at 500°C for 3 hours, then the temperature is increased to 700°C and kept for 10 hours.

[0056] (6) The sintered material was added to a ball mill and ground for 2 h to obtain a polyanion type sodium ion battery positive electrode material with a chemical formula of Na 7 Ba 0.9 V 3.6 (P 2 O 7 ) 4 O 1.8 / C.

[0057] The positive electrode material prepared in this embodiment is used as the working electrode, sodium is used as the counter electrode, and a button cell is assembled. At a current density of 80 mA / g, the first cycle specific capacity is 73 mAh / g. After 50 cycles, the specific capacity can be maintained at 66 mAh / g.

[0058] Comparative Example 1

[0059] This comparative example prepares a polyanion type sodium ion battery positive electrode material, which is different from Example 3 in that a direct sintering method is used, and the specific process is as follows:

[0060] (1) 3.5 kg of ammonium dihydrogen phosphate, 1.6 kg of ammonium metavanadate, 3.57 kg of sodium oxalate, 0.675 kg of barium carbonate and 4.93 kg of glucose were mixed and ground. The mixed materials were placed in a muffle furnace, isolated from air and kept at 500° C. for 3 hours, and then heated to 700° C. and kept for 10 hours.

[0061] (2) The sintered material is added to a ball mill and ground for 2 hours to obtain a polyanion sodium ion battery positive electrode material.

[0062] The positive electrode material prepared in this embodiment is used as the working electrode, sodium is used as the counter electrode, and a button cell is assembled. At a current density of 80 mA / g, the first cycle specific capacity is 54.75 mAh / g. After 50 cycles, the specific capacity can be maintained at 46.2 mAh / g.

[0063] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A method for preparing a polyanion sodium ion battery positive electrode material, characterized in that: The following steps are involved: The phosphorus source, vanadium source, sodium source and carbon source are dissolved in water and then spray-dried to prepare particles; The barium source is dissolved in an organic acid to obtain a solution A, the solution A is evaporated to obtain a solid B, and the solid B is added to ethanol to dissolve to obtain a solution C; The particles are mixed with solution C and evaporated to dryness to obtain a dry material; The dried material is sintered in an air-tight condition to obtain the polyanion type sodium ion battery positive electrode material; The barium source is at least one of barium carbonate and barium hydroxide; the molar ratio of the barium element in the barium source to the vanadium element in the vanadium source is (0.01-0.2):1; The organic acid is at least one of citric acid, formic acid, acetic acid or propionic acid; The sintering process is to keep the dried material at 450-500° C. for 2-4 hours, and then raise the temperature to 550-800° C. and keep it for 8-12 hours.

2. The preparation method according to claim 1, characterized in that: The phosphorus source is at least one of sodium pyrophosphate, phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, sodium monohydrogen phosphate or sodium dihydrogen phosphate.

3. The preparation method according to claim 1, characterized in that: The vanadium source is at least one of vanadium trioxide, vanadium pentoxide, ammonium metavanadate, vanadyl acetylacetonate or vanadium acetylacetonate.

4. The preparation method according to claim 1, characterized in that: The sodium source is at least one of sodium carbonate, sodium acetate, sodium oxalate, sodium pyrophosphate, sodium monohydrogen phosphate or sodium dihydrogen phosphate.

5. The preparation method according to claim 1, characterized in that: The carbon source is at least one of glucose, citric acid, oxalic acid, lactose or galactose.

6. The preparation method according to claim 1, characterized in that: The molar ratio of Na, V and P elements in the sodium source, vanadium source and phosphorus source is (1-5): (1.01-1.2): (2-4).

7. The preparation method according to claim 1, characterized in that: The molar ratio of the carbon source to the vanadium source is 1-2.

Citation Information

Patent Citations

  • Preparation method of carbon coated vanadium sodium phosphate positive electrode material

    CN105336924A

  • Metal-doped Na3V2(PO4)3 composite electrode material and preparation method and application thereof

    CN107611390A

  • Carbon-coated NaxRyM2(PO4)3 material and preparation and application thereof

    CN109841801A

  • Sodium vanadium phosphate composite cathode material and preparation method thereof

    CN111994890A

  • Pyrophosphate composite material, preparation method and application thereof, and sodium ion battery

    CN113328086A